2017
DOI: 10.1111/ppa.12718
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Meloidogyne paranaensis populations and their aggressiveness to susceptible coffee genotypes

Abstract: Meloidogyne paranaensis is one of the most destructive root-knot nematode (RKN) species parasitizing coffee in Brazil and in the Americas generally. The objectives of this study were to assess the genetic variability, aggressiveness and virulence of seven different M. paranaensis populations on susceptible and resistant Coffea spp. All seven RKN populations were identified by biochemical and molecular methods. Coffee seedlings were inoculated in the greenhouse, and the nematode reproduction factor was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 26 publications
4
24
0
3
Order By: Relevance
“…(1) 2Coffee Science, 15:e151708, 2020 susceptibility of these clones. The use of susceptible clones is also important to check on the inoculum's virulence, understood as the pathogen's ability to multiply within the host (Lima et al, 2015;Peres et al, 2017;Santos et al, 2018b). These results are similar to those obtained by Santos et al (2017; who observed reproduction factor averages of 0.36 and 1.59 in different experiments evaluated in Western Amazonia.…”
Section: Resultssupporting
confidence: 85%
“…(1) 2Coffee Science, 15:e151708, 2020 susceptibility of these clones. The use of susceptible clones is also important to check on the inoculum's virulence, understood as the pathogen's ability to multiply within the host (Lima et al, 2015;Peres et al, 2017;Santos et al, 2018b). These results are similar to those obtained by Santos et al (2017; who observed reproduction factor averages of 0.36 and 1.59 in different experiments evaluated in Western Amazonia.…”
Section: Resultssupporting
confidence: 85%
“…This difference in the value of the RF may be related to the physiological differences in the nematode aggressiveness. Santos et al (2018) demonstrated that among M. paranaensis populations, there are differences in pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes MG 0179‐1R1‐776 and MG 0179‐3R1‐151, from the breeding programme of EPAMIG, were selected because of their resistance to M. paranaensis (Peres et al, 2017). The commercial cultivar Catuaí Amarelo IAC 62 was used as a susceptible control, and the commercial cultivar IPR‐100, which is derived from a cross between C. arabica × C. liberica and has resistance genes inherited from C. liberica , was used as a resistant control (Sera et al, 2017; Santos et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Among several species that parasitize coffee plants, Meloidogyne paranaensis (Carneiro et al, 1996) is especially important, hindering plant growth and causing losses of approximately 35% in yield (Lopez-Lima et al, 2015). The damage can be even higher depending on the level of attack and on the genetic variability within nematode population (Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%